2014
DOI: 10.1109/tuffc.2014.006649
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of galileo signals for time metrology

Abstract: Using global navigation satellite system (GNSS) signals for accurate timing and time transfer requires the knowledge of all electric delays of the signals inside the receiving system. GNSS stations dedicated to timing or time transfer are classically calibrated only for Global Positioning System (GPS) signals. This paper proposes a procedure to determine the hardware delays of a GNSS receiving station for Galileo signals, once the delays of the GPS signals are known. This approach makes use of the broadcast sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The antenna cable is commonly considered a non-dispersive medium (Defraigne et al 2014). However, Dyrud et al (2008) showed that a small constant variation of 0.004 m or approximately 13 ps (picoseconds) can exist in the absolute DCB of the receiver system while working with different cable lengths.…”
Section: Cable Dcbmentioning
confidence: 99%
“…The antenna cable is commonly considered a non-dispersive medium (Defraigne et al 2014). However, Dyrud et al (2008) showed that a small constant variation of 0.004 m or approximately 13 ps (picoseconds) can exist in the absolute DCB of the receiver system while working with different cable lengths.…”
Section: Cable Dcbmentioning
confidence: 99%
“…During the TVF In-Orbit-Validation phase [1] a method to evaluate the Galileo receiver delay in E5 was proposed and developed by the Observatoire Royal de Belgique (ORB) [2], assuming that the GPS delays in L1 and L2 are known and that the receiver delay in Galileo E1 is known or is the same as the GPS L1 delay. Differential Code Biases (DCBs) for GPS and Galileo satellites are also assumed to be available.…”
Section: Methods Overviewmentioning
confidence: 99%
“…The method is based on pseudorange data processing exclusively, without any need of instrumental intervention at the receiver site. The method description and formulation is fully described in [2] and only the key facts and main equation are summarized and adapted here.…”
Section: Methods Overviewmentioning
confidence: 99%
“…the hardware delays of the GNSS signals inside the antenna, the antenna cable and the receiver [8] [8] . Two methods can be used: absolute or relative.…”
Section: Service#5: User Gnss Receiver Calibrationmentioning
confidence: 99%